TOPOGRAPHIC ANATOMY OF THE CRANIAL NERVES AND THEIR SIGNIFICANCE IN SURGICAL PRACTICE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The topographic anatomy of the cranial nerves plays a decisive role in neurosurgical practice, particularly in diagnosis, selection of surgical approaches, and ensuring intraoperative safety. This analytical review examines the anatomical trajectories of all 12 pairs of cranial nerves, their topographic relationships with adjacent structures, and the major risk zones encountered during clinical and surgical procedures. Although modern radiologic visualization techniques have significantly improved the accuracy of anatomical assessment, surgical errors related to topographic variations still occur in 12–17% of operations. The analysis is based on clinical studies, meta-analyses, and statistical reports published over the last decade.